2012
DOI: 10.1002/aoc.2854
|View full text |Cite
|
Sign up to set email alerts
|

The influence of some triphenylantimony(V) catecholates and o‐amidophenolates on lipid peroxidationin vitro

Abstract: A number of catecholates (complexes 1-3, 6) and o-amidophenolates (complexes 4, 5) of triphenylantimony(V) was examined in the process of lipid peroxidation of liver homogenates and sperm of Russian sturgeon (Acipenser gueldenstaedti B.), and human red blood cells. It was shown that the influence of complexes 1-6 on lipid peroxidation process in model systems depends on the nature of redox-active ligand and varies from weak anti-and pro-oxidant (catecholates 1, 6) to pronounced antioxidant (catecholates and o-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…The level of lipid peroxidation was estimated in the course of non‐enzymic reaction promoted by the ‘ascorbic acid–(NH 4 ) 2 Fe(SO 4 ) 2 ’ system. It is shown that the initial complex 1 (Table ) decreases the lipid oxidation of organ tissue homogenates by 10–35% compared with the control experiment, corresponding to earlier results on hydrobiont tissues . The different percentage of inhibition indicates the tissue specificity of 1 : the maximum reduction of TBARS concentration was observed in the case of heart homogenate.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The level of lipid peroxidation was estimated in the course of non‐enzymic reaction promoted by the ‘ascorbic acid–(NH 4 ) 2 Fe(SO 4 ) 2 ’ system. It is shown that the initial complex 1 (Table ) decreases the lipid oxidation of organ tissue homogenates by 10–35% compared with the control experiment, corresponding to earlier results on hydrobiont tissues . The different percentage of inhibition indicates the tissue specificity of 1 : the maximum reduction of TBARS concentration was observed in the case of heart homogenate.…”
Section: Resultssupporting
confidence: 75%
“…Potentially produced metabolites are able to promote the LP process. Earlier we confirmed in experiments in vitro that organometallic derivatives – Ph 3 Sb, Ph 3 SbBr 2 – promote theprocess of LP . Antimony(V) compounds in biosystems can undergo reduction to Sb(III) in interaction with low‐molecular‐weight thiols (cysteine, glutathione) and SH protein groups, resulting in ROS induction and intensifying the LP process.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…4, 5 The biolog ical activity of these compounds has been studied. [6][7][8] Antimony compounds are characterized by a diversity of coordination modes and structure types. In the absence of strong steric hindrance, pentacoordinate Sb V deriva tives are prone to complete the coordination number to six through intermolecular interactions or through the coor dination by additional neutral ligands.…”
mentioning
confidence: 99%
“…Previously we showed that the redox characteristics, antiradical activity of organo-antimony(V) complexes with redox-active ligands, as well as their ability to bind molecular oxygen depends on a variety of factors [1][2][3][4][5][6]. Electron-donating substituent group in the redox-active fragment facilitates O 2 binding, shifts anodic oxidation potentials to the cathodic region, and enhances the antiradical activity of Sb(V) compounds [7,8].…”
mentioning
confidence: 99%